Metoda Diskusi Sebagai Upaya Melambungkan Kesadaran Masyarakat Terhadap Urgensi Kesehatan Jiwa - Ira Kusumawaty; Podojoyo; Yunike; Eprila; Peni Cahyati; Dudi Hartono (Empowerment: Jurnal Pengabdian Masyarakat, 2022)
People's mental health problems often do not get adequate attention so that they have an impact on the deterioration of the quality of life. It is necessary to increase public awareness of the importance of mental health, but the steps to equalize public perception are still very limited. This service activity aims to equalize understanding of the urgency of maintaining mental health through the application of discussion methods. The discussion, which was attended by 23 participants, covered the stages of preparation, implementation and evaluation. The preparation stage has involved various parties, from the neighborhood level to the sub-district level, community leaders, religious leaders and community groups. At the implementation stage, the discussion begins with brainstorming, explanations about mental health and the preparation of the organizational structure of the mental health post. The residents seemed enthusiastic, accompanied by the support of policy makers and the coordination of related parties. At the evaluation stage, participants' understanding of the importance of mental health increased and commitments and work programs were agreed upon to support the establishment of mental health posts. This activity has implications for improving the mental health condition of the community through community empowerment by solving community mental health problems collectively.